2016
DOI: 10.1021/acs.jpclett.6b02346
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Cellobiose in Aqueous Alkali and the Mechanism of Cellulose Dissolution

Abstract: Cellulose, one of the most abundant renewable resources, is insoluble in most common solvents but dissolves in aqueous alkali under a narrow range of conditions. To elucidate the solubilization mechanism, we performed electrophoretic NMR on cellobiose, a subunit of cellulose, showing that cellobiose acts as an acid with two dissociation steps at pH 12 and 13.5. Chemical shift differences between cellobiose in NaOH and NaCl were estimated using 2D NMR and compared to DFT shift differences upon deprotonation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…This can be explained by that the OH 2 hydroxyl group is equatorial in Glc, but axial in Man. Similar coordination has been seen previously in simulations of cellobiose, and has been suggested to induce deprotonation of cellulose in alkali solvents systems (Bialik et al 2016;Lindman et al 2017). Furthermore, Glc experienced an even higher coordination of OH -in the Gal substituted oligomer (MGLM), possibly a consequence of that the Glc and Gal groups can coordinate a OH -together as showed in Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This can be explained by that the OH 2 hydroxyl group is equatorial in Glc, but axial in Man. Similar coordination has been seen previously in simulations of cellobiose, and has been suggested to induce deprotonation of cellulose in alkali solvents systems (Bialik et al 2016;Lindman et al 2017). Furthermore, Glc experienced an even higher coordination of OH -in the Gal substituted oligomer (MGLM), possibly a consequence of that the Glc and Gal groups can coordinate a OH -together as showed in Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The purpose was to investigate if the Gal substitution affected the interaction between OH -and the backbone hydroxyl groups. Previous work on cellobiose has also showed that deprotonation of the hydroxyl group is likely to occur on C2 (Bialik et al 2016). The C2 hydroxyl group is of largest interest since alkaline hydrolysis of the glycosidic linkage has been Fig.…”
Section: Composition and Properties Of Extracted Ggm And Mannan Modelmentioning
confidence: 99%
“…However, in light of the lack of frustration in aqueous systems (Medronho et al 2012), this appears unlikely. An alternative explanation for the presence of charge on the cellulose chains is provided by the recent observation that cellulose is deprotonated in aqueous alkali (Bialik et al 2016), as anticipated by Lindman et al (Medronho and Lindman 2014;Alves et al 2015). Thus, we argue that only the role of the TBA þ cation is similar between the TBAAc/DMSO and TBAH/water solvent system; the primary driving forces for cellulose dissolution are distinct.…”
Section: Discussionmentioning
confidence: 47%
“…[97][98][99][100] Recently, more conclusive evidence for ionization at high pH has been obtained by Bialik et al in studies on model systems. 101 To elucidate the dissolution mechanism, these authors performed electrophoretic NMR on cellobiose, a subunit of cellulose, showing that cellobiose acts as an acid with two dissociation steps at pH 12 and 13.5 (Fig. 2, left).…”
Section: Does Cellulose Ionization Contribute To Solubility In Water?mentioning
confidence: 99%
“…However, Bialik et al found that ionization does not depend on whether NaOH or KOH is used to obtain a particular pH. 101 A larger amount of KOH is, however, needed to obtain the same pH because NaOH is a stronger base. Hence, the apparent cation specificity previously reported 102,103 What can we learn from cellulose derivatives?…”
Section: Does Cellulose Ionization Contribute To Solubility In Water?mentioning
confidence: 99%